Effect of Osmotic Dehydration and Drying Air Temperatures on the Quality of Dried White Button Mushroom - Murumkar, R P; Jain, S K; Pisalkar, P S; Verma, R C (Journal of Agricultural Engineering, 2007)
Experiments were conducted on air drying of button mushroom osmotically dehydrated in 10, 15 and 20 per cent sodium chloride (NaCl) concentration to investigate the effect of osmotic dehydration and drying air temperatures on drying characteristics of mushroom and the quality of dried mushroom. Drying was accomplished in fluidized bed dryer at 35, 40 and 50degree C temperatures. The time required for drying of osmotically dehydrated mushroom to 15 to 18 per cent moisture content was found to be 5.5 to 11 h. The rate of drying increased with the increase in drying temperature. Increase in drying temperature significantly reduced the total drying time. Osmotic dehydration in NaCl had influence on the water activity of the final product. Similarly, ethylene diamine tetra acetic acid (EDTA) and potassium metabisulphate (KMS) had influence on the amino acid content, colour and rehydration ratio. EDTA treated samples were recommended on the basis ofamino acid content and KMS treatment improved the colour of the dried mushroom. A loss of approximately 1.4 mg of ascorbic acid was observed during drying.